Violent Dissent and Rebellion in Africa - Carey, Sabine C (SAGE Publications/PRIO, 2007)
This article analyzes how the selection process for the executive affects the risk of rebellion and insurgencies in sub-Saharan Africa between 1971 and 1995. Four executive recruitment processes are distinguished, which are characteristic for the African context: (1) a process without elections, (2) single candidate elections, (3) single party, multiple candidate elections, and (4) multiparty executive elections. The results suggest that single candidate elections and multiparty elections substantially reduce the risk of insurgencies compared to systems without any kind of executive elections. They further show that during times of political instability the risk of large-scale violent dissent increases substantially. The article supports findings of the civil war literature that higher levels of income are associated with a lower risk of intrastate violence, while oil-exporting countries are at a higher risk of rebellion. In short, this article further strengthens the need to use more specific measures of elements of political regimes, which also take into account regional particularities, in order to paint a more informative picture of how political structures influence the risk of internal violence.